Galatians 1:8 and Paul’s Reading of Abraham’s Story - Ehorn, Seth M. (The journal of theological studies, 2013)
What accounts for Paul’s elusive mention of ‘an angel from heaven’ in Gal. 1:8? Interpreters have typically avoided the question altogether or posited that Paul’s opponents claimed that their counter-gospel (Gal. 1:6–7) was mediated by angels (cf. Gal. 3:19). In this short essay, I suggest that Paul’s opaque reference becomes more clear when read in the light of his large-scale reflection on the Abrahamic narrative in his letter to the Galatians. It is from the story of Abraham that Paul finds reference to angelic visitors who come bringing a message that agrees with a promise already delivered to Abraham (Gen. 18:10, 14; cf. Gen. 17:16–17).